Evaluation of inflammatory processes by FTIR spectroscopy - Rodrigues, Laís Morandini [UNESP]; Carvalho, Luís Felipe das Chagas e Silva; Bonnier, Franck; Anbinder, Ana Lia [UNESP]; Martinho, Herculano da Silva; Almeida, Janete Dias [UNESP] (Taylor & Francis, 2018)
Fourier transform infrared (FTIR) spectroscopy is a powerful diagnosis technique and has been used to identify patterns of molecular changes based on vibration modes. The objective of this study was to evaluate inflammatory fibrous hyperplasia (IFH) lesions and oral normal mucosa (NM) initially with histopathological exam and then using micro-FTIR spectroscopy to analyse the samples. Eleven IFH and 11 NM samples were analysed at five different points to cover the largest area possible by the micro-FTIR technique. Bands were observed between 970 and 1743 cm−1 which corresponded to different structural components like collagen, lipids, fatty acids, proteins and amino acids. Spectral bands were more intense mostly for IFH lesions, including collagen bands, which are an important component of inflammatory fibrous hyperplasia. This study demonstrated that differentiation in the inflammatory tissue was observed in FTIR spectral differences, in terms of biochemical composition.
Keywords: diagnosis; FTIR spectroscopy; inflammatory processes